دور نظم المعلومات التسويقية في دعم وترشيد قرارات الترويج دراسة ميدانية على قطاع الصناعات الهندسية في مدينة حلب - ميّا, علي; شيخ ديب, صلاح; بليلو, جمال (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتناول هذه الدراسة، تقويم دور نظام المعلومات التسويقية في دعم وترشيد قرارات المزيج الترويجي في قطاع الصناعات الهندسية في مدينة حلب، بغية تحسين كفاءة نظام المعلومات التسويقية في تزويد صانعي القرار بمعلومات تعبر عن كل متغيرات البيئة الخارجية بغية صنع قرارات ترويجية فعالة، كون الترويج يمتلك التأثير المباشر الأكبر على المبيعات. ولذلك اشتملت الدراسة على تحديد أنواع القرارات المتعلقة بتحديد المزيج الترويجي الأمثل لمنتجات المنظمة وبيان دور نظام المعلومات التسويقية في دعم قرارات الترويج.إضافة إلى ذلك تمّ إجراء دراسة ميدانية عن طريق تصميم قائمة استقصاء وزعت على شركات الصناعات الهندسية في مدينة حلب، كما خلصت الدراسة إلى مجموعة من النتائج والتوصيات التي من شأنها رفع مستوى أداء نظام المعلومات التسويقية في تزويد صانعي القرار بمعلومات كاملة ودقيقة تدعم اختيارهم للبديل الأمثل. This study investigates assessment of role of the marketing information system in the supporting and rationalization of the promotion mix decisions, for improving efficaciousness of the Marketing Information Systems in providing marketing decisions makers by information about all of variables of outside environment for making effective promotion decisions, because this element of the marketing mix has the most direct influence on sales. Thus, the study consists of the following: § Defining the kinds of quintessential promotional mix decisions for organization products. § Explaining role of the marketing information systems in supporting of promotional mix decisions. § Afield study by designing a questionnaire which is distributed to companies of engineering industries in Aleppo. § Summary of results and recommendations aiming at increasing the level of performance marketing information system in providing marketing decisions makers by information about all of variables of outside environment for making effective promotion decisions.